COVID‐19: The immediate response of european academic dental institutions and future implications for dental education. (13th July 2020) - Quinn, Barry; Field, James; Gorter, Ronald; Akota, Ilze; Manzanares, Maria‐Cristina; Paganelli, Corrado; Davies, Julia; Dixon, Jonathan; Gabor, Gerber; Amaral Mendes, Rui; Hahn, Petra; Vital, Sibylle; et al.
Abstract: The COVID‐19 pandemic has had an immediate and dramatic impact on dental education. The Association of Dental Education in Europe decided to carry out an investigation to assess the immediate response of European Academic Dental Institutions. An online survey was sent to both member and non‐member dental schools to investigate the impact on non‐clinical and clinical education, assessment and the well‐being/pastoral care measures implemented. The preliminary findings and discussion are presented in this paper, for the responses collected between the 25 March and 5 April 2020. The survey at this time of publication is ongoing, and detailed results can be accessed https://adee.org/covid‐19‐european‐dental‐education%E2%80%99s‐immediate‐response .